Implementation of Expenditure Standards Analysis (Case Study on The Regional Government of Tolitoli Regency, Central Sulawesi Province) - Nurul Fadila; Rahma Masdar; Haryono Pasang Kamase; Selmita Paranoan; Masrudin Masrudin; Arif Gunarsa (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the reasonableness of costs for performance report preparation programs in each Regional Government Organization (OPD) of Tolitoli Regency. The approach used is descriptive quantitative, with secondary data in the form of the 2024 Tolitoli Regency Regional Government Work Plan (RKPD) document. Data analysis was carried out using simple linear regression with the help of SPSS software. The results show that the regression equation obtained is: Y =-22,780,831,863,267 + 3,665,682,455,393X, where X represents the number of performance report preparation activities/reports and the summary of OPD performance realization as a cost driver. Based on the estimation results, 3 OPDs are in the underfinancing category, 20 OPDs are in the overfinancing category, and 6 OPDs are in the reasonable cost category. These findings indicate that there is still an imbalance in the allocation of expenditure budgets in Tolitoli Regency. The implementation of ASB (Expenditure Standards Analysis) is expected to help the regional government to prepare a budget that is more effective, efficient, and on target, while also increasing transparency and accountability in the use of public funds.